KAJIAN KELAYAKAN TEKNIS DAN FUNGSIONAL JEMBATAN PENYEBERANGAN ORANG DI RUAS JALAN BANDUNG–SUMEDANG - Ignatius Malvio Sugiharta; Andi Muhammad Mufadhdhal (CRANE: Civil Engineering Research Journal, 2025)
The growth of educational activities and urban mobility in the Jatinangor area has significantly increased traffic intensity and the risk of pedestrian accidents, particularly along the Bandung–Sumedang Highway. This study aims to evaluate the technical and functional feasibility of constructing a pedestrian bridge (JPO) and to compare it with the alternative of a pelican crossing as a more adaptive pedestrian solution. The research methods include field surveys, analysis of pedestrian behavior and traffic flow, as well as multi-criteria assessments of both alternatives based on safety, cost efficiency, accessibility, and utilization levels. The findings indicate that although the pedestrian bridge meets technical requirements, its effectiveness is limited due to low utilization rates and poor accessibility for vulnerable groups. In contrast, the pelican crossing is considered more suitable for medium-capacity roads with high pedestrian volumes, as it offers greater efficiency, inclusivity, and lower costs. These results support the hypothesis that the pelican crossing provides a more appropriate solution for improving pedestrian safety in the study area, while also offering recommendations for context-sensitive and sustainable traffic infrastructure planning.